Offshore Petroleum Developments in Northwest Europe — An Update - Skipper, Keith (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1977)
Summary The North Sea has been the focus of attention during the last decade for petroleum developments on the continental shelves of northwest Europe. The North Sea petroleum basin is ranked as one of the richest in the world. Production of North Sea gas commenced in 1966 and North Sea oil in 1971. By the early 1980s, 20 per cent of Western Europe's total oil requirements will be supplied by the North Sea. This will have beneficial effects not only on the economies of the United Kingdom and Norway (which will be self-sufficient in oil) but will also buy time to develop alternate sources of energy. A characteristic of North Sea petroleum development programs is their high cost making North Sea oil the most expensive conventionally produced crude oil to date. To meet the demands of sea and climatic conditions, new offshore production technology has evolved. In the northern North Sea, the favorable condition which exist for large reserves of oil include adequate Jurassic source rocks, good shale seals and large structures with highgrade sand reservoirs (mainly of Middle, Upper Jurassic, and Tertiary age) developed in a long north-south trending medial graben. Upper Permian salt seals large accumulations of natural gas in sandstone reservoirs of Lower Permian age in the southern North Sea. Similar tectonic and sedimentary relationships may exist in other basins of the northwest European shelf (off northern Norway, western Ireland, southwest and west UK) and these areas will receive future exploration attention.